Review: Status of wild elephant, conflict and conservation actions in Thailand - RONGLARP SUKMASUANG; NARIS PHUMPAKPHAN; PRATEEP DEUNGKAE; RATTANAWAT CHAIYARAT; MANANYA PLA-ARD; NORASET KHIOWSREE; KHWANRUTAI CHARASPET; PAANWARIS PAANSRI; JESADA NOOWONG (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sukmasuang R, Phumpakphan N, Deungkae P, Chaiyarat R, Pla-Ard M, Khiowsree N, Charaspet K, Paansri P, Noowong J. 2024. Review: Status of wild elephant, conflict and conservation actions in Thailand. Biodiversitas 25: 1479-1498. This study comprehensively reviewed various aspects of population status, distribution, conflict situations, and conservation strategies for managing human-elephant conflicts (HECs). The primary goal is to foster a clear understanding of the current status, issues, and problem-solving approaches to benefit elephant conservation and management. The key element in elephant conservation is the acceptance of the coexistence between humans and elephants in their respective areas. Managing overlapping areas between humans and elephants is crucial for conservation efforts. A major concern is that elephants venture outside protected areas, increasing risk to both human and elephant populations. Therefore, enhancing the efficiency of conflict management is of the utmost importance to the long-term survival of elephants. This study revealed that vital approaches for managing elephant populations in Thailand include designating conservation areas as the foundation for long-term elephant conservation. In addition, habitat management at the population level, implementing compensation schemes, establishing community-based monitoring groups in conflict areas, improving conflict management practices, and decentralizing decision-making processes in conservation efforts are critical. Other essential elements of successful conservation and management in Thailand include setting population targets for elephants in each conservation area, with the goal of effective management. This was supported by research, community collaboration, decentralization, and performance evaluation to gauge the success of implemented measures in reducing HECs by assessing the number of conflict incidents and fatalities for both humans and elephants. This suggests the need for a fundamental reform of the elephant conservation policy.